Reflective practice and participant involvement in research. Issue 4 (4th July 2019) - Jones, Phil; Charitou, Christos; Mercieca, Daniel; Poblete Nunez, Ximena
ABSTRACT: This article discusses the relationships between reflective practice and research for professionals who are research participants. It offers an analysis of the opportunities for reflective practice created for participants through their involvement in research. Three examples of research into professional's perspectives on practice with children in Chile, Malta and Cyprus are presented and analysed. The analysis of the three examples shows the role research can have in creating particular kinds of spaces and relationships that facilitate reflection and how it can introduce dimensions that are normally excluded from critical reflection within a profession. The examples show this as involving: reparative and augmented critical reflection; new information and meaning making and the interactions between macro, meso and micro perspectives.